2018
DOI: 10.1186/s12890-017-0571-7
|View full text |Cite
|
Sign up to set email alerts
|

Burden of asthma and COPD overlap (ACO) in Taiwan: a nationwide population-based study

Abstract: BackgroundPatients with symptoms of both asthma and chronic obstructive pulmonary disease (COPD) may be classified with the term asthma-COPD overlap (ACO). ACO is of considerable interest as it is currently poorly characterised and has been associated with worse health outcomes and higher healthcare costs compared with COPD or asthma alone. Patients with ACO in Asia remain poorly described, and there is limited information regarding their resource utilisation compared with patients with asthma or COPD only. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 45 publications
10
31
0
Order By: Relevance
“…Similar results were reported by other studies . Montes de Oca et al evidenced that the number of exacerbations was 4.9 times higher in patients with ACO, while Kang et al found that these patients suffered more frequent and more severe exacerbations, resulting in a higher number of hospital admissions.…”
Section: Asthma‐copd Overlapsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar results were reported by other studies . Montes de Oca et al evidenced that the number of exacerbations was 4.9 times higher in patients with ACO, while Kang et al found that these patients suffered more frequent and more severe exacerbations, resulting in a higher number of hospital admissions.…”
Section: Asthma‐copd Overlapsupporting
confidence: 86%
“…A retrospective study carried out in Taiwan showed that patients with ACO had more exacerbations (35.3%) than patients with asthma (29.0%, P < 0.0001 vs ACO) or COPD alone (18.6%, P < 0.0001 vs ACO). ACO patients had a higher rate of exacerbations requiring emergency room visits (8.2% vs 2.7% for the patients with COPD, P < 0.0001 and 2.3% for the asthma patients, P < 0.0001) and intensive care unit treatment (4.3% vs 2.7% for the patients with COPD, P < 0.0001 and 0.5% for the patients with asthma, P < 0.0001) …”
Section: Asthma‐copd Overlapmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to the relationship between socioeconomic status (SES) and health care outcomes [38,39], insurance premiums were used as a proxy for SES because the NHI claims data set does not provide patients' educational levels or household incomes. In addition, health status and disease severity may affect the measurement of health outcomes [6,9,16,39]; therefore, any history of hypertension (ICD-9-CM codes 401.xx-405.xx), and diabetes (ICD-9-CM codes 250.xx) [4,6,9], whether a patient had ED visits for COPD or asthma and whether a patient was hospitalized for COPD or asthma were included in the previous year of the index date. The Charlson comorbidity index (CCI) [4,5,7,40] that was calculated for each patient according to outpatient or inpatient care by using the Quan adaptation of the Elixhauser comorbidities [41] and the number of outpatient visits for COPD or asthma (3-12, 13-24, and ≥25 times) [16] was measured during the COC period.…”
Section: Covariatesmentioning
confidence: 99%
“…Studies of ACO reported the prevalence ranges from 0.9% to 11.1% among general population around the world [3]. The disease burden and healthcare utilization such as emergency department (ED) visits and hospital admissions for patients with ACO has been found to be higher than those with asthma or COPD alone [4][5][6][7][8][9]. While the importance of caring for patients with ACO has become a critical issue, there is limited information regarding treatment in ACO patients to reduce the resulting healthcare utilization.…”
Section: Introductionmentioning
confidence: 99%